Break even point analysis of cireng lava gisting msmes - Purwanto, Purwanto; Wagiyo, Wagiyo; Arohman, Arohman; Juliono, Juliono (Institute of Computer Science (IOCS), 2025)
One of the MSME Home Industries, Cireng Lava Gisting, which is part of the Molagi Nyemil brand, produces several types of cireng filled with spicy shredded chicken, intestine gizzards, meatballs and sausages. The research method used is a descriptive research method with a quantitative approach. The sample in this research is a financial report in the form of a balance sheet and profit and loss report for MSME Cireng Lava Gisting in 2024. To find out how much costs are incurred to produce products, so that the business makes a profit or at the break-even point, it is necessary to carry out calculations using break even point (BEP) can measure profit. The lowest variable costs for intestinal gizzard contents are IDR 4,956 BEP 1,758 units, sales in 2024 are compared with 2023 which experienced an increase of 33% from 7,825 units to 9,725 units, profit in 2023 IDR 28,080,162,- to IDR 40,184,900,- BEP 2,053 units of shredded chicken filling with variable costs of Rp. 5,681,- profit in 2023 of IDR. 63,989,211,- in 2024 Rp. 106,561,594,- The Cireng product filled with shredded chicken is the fastest product to achieve BEP as well as the product that produces the largest profit compared to other types of products. BEP 2,271 units, namely variable cost meatball content Rp. 6,096,- profit in 2023 is Rp. 13,224,865,- and in 2024 Rp. 21,121,346,- an increase of Rp. 7,896,481,- or 60%, Cireng with sausage filling with variable costs Rp. 7,271,- BEP in 3,249 units in 2023 was achieved in the 8th month, in 2024 at the beginning of the 7th month, where total sales in 2023 were IDR. 50,490,000,- in 2024 to Rp. 67,720,000,- 96% increase in profit from IDR 4,11,562,- to IDR 9,613,917